ナンタイヨウ ニ オケル コウセツ ノ サンソ アンテイ ドウイタイヒ ノ ケイド ブンプ ト キセツ ヘンカ - 中村, 佳代; カナムラ, カヨ; 青木, 茂; アオキ, シゲル; 豊田, 威信; トヨタ, タケノブ; 青山, 雄一; アオヤマ, ユウイチ; Nakamura, Kayo; Aoki, Shigeru; Toyota, Takenobu; Aoyama, Yuichi (2010)
P(論文) 降雪の酸素安定同位体比(δ^<18>O)の緯度分布と季節変化の存在はよく知られているが,極域海洋上での降雪のδ^<18>O の報告はほとんどない.本研究では,南大洋高緯度域において,夏季と冬季の4つの現場海洋観測の機会を利用し,船上に降った雪を採取し分析した.また,通年のデータとして,2008年における昭和基地での降雪のサンプルを分析した.これらに基づいて,南大洋上の降雪のδ^<18>O の緯度分布と季節変化について考察する.全般に高緯度ほど低く,また夏季より冬季の方が低いδ^<18>O の分布が得られた.また,緯度変化の傾きは冬季の方が強い.夏季および冬季のδ^<18>O は,60°Sにおいて-5.4‰と-11.3‰であるのに対し,66°Sにおいて-10.5‰と-20.8‰であった.これらの結果は,南極海での塩分分布やその変化のメカニズムを解明する上での手助けになると考えられる. The stable oxygen isotope ratio(δ^<18>O) in precipitation is known to have important meridional and seasonal variations, but there are almost no measurements of δ^<18>O in precipitation over polar oceans. The present research took advantage of 4 opportunities for in situ observations in summer and winter at high latitudes in the Southern Ocean. In addition, we analyzed samples of precipitation at Syowa Station in 2008 to obtain year-round data. Based on these data, we consider the meridional and seasonal variations of δ^<18>O in precipitation over the Southern Ocean. In general, δ^<18>O decreases with increasing latitude, and is lower in winter than in summer. The latitude gradient is stronger in winter. At 60°S, δ^<18>O is -5.4‰ and -11.3‰ in summer and winter, respectively, while the corresponding figures at 66°S are -10.5‰ and -20.8‰. These results will help us understand the mechanisms of the salinity distribution and its variation in the Antarctic Ocean. departmental bulletin paper